The economic impact of the education and health sector on a rural community's economy - Gerald A. Doeksen; Mike Woods (European Regional Science Association (ERSA), 2002)
Many rural communities in the USA are economically depressed due to declining employment opportunities. Some of the causes include increased agricultural mechanization and consolidation, declining manufacturing jobs, inability to attract high tech jobs, and declining mineral prices. Whatever the cause, it is crucial that rural community leaders have their community as attractive as possible for whatever development strategy they pursue. Research supports the fact that to attract business and industry, education and health services are critical quality of life factors important in final location decisions. Likewise, if attracting retirees is a development strategy, research indicates that health and safety are important quality of life variables. The objective of this paper is to demonstrate how important the education and health sectors are to the economy of a rural community. This will be accomplished by utilizing a county input-output model. The model has five health sectors (hospitals, physicians, nursing homes, pharmacies, and other) and two education sectors (primary and secondary education and vocational education). The model will estimate income and employment impacts of the health and education sectors. In addition, the model will project the impact that these sectors have on community retail sales. The model uses readily available data from IMPLAN. Thus, the study can easily be replicated in U.S. counties and communities. The paper will present results of the application of the model to Atoka County, a rural county in southeastern Oklahoma. The 2000 census population fir Atoka was 13,879 with the largest community having 2,988 residents. Health and education employment and income data (wages and salaries and proprietor income) were collected directly from county businesses. The input-output model was run to measure the indirect and induced impacts. The results show how important these sectors are to jobs and income as well as the services they provide. Direct employment in the health and education sectors was approximately 17 percent of the total county employment and income base. Adding the indirect and induced impacts brings the total impact of these sectors to about 25 percent. It also must be recognized that these sectors are growing and many jobs are above the county's average wage rate. The results of this study can be used to demonstrate to local residents the importance of the health and education sectors to the local economy and why they should support these sectors. Local residents need to be encouraged to use local health services such that these services are provided locally and remain economically viable. Also, if local tax support is needed for health or education services, the study will document the importance of these sectors to the local economy.
Keywords: 330